Cost-Effectiveness of Treatments after Closed Extraarticular Distal Radius Fractures in Older Adults from the WRIST Clinical Trial. Issue 2 (24th November 2020) - Yoon, Alfred P.; Shauver, Melissa J.; Hutton, David W.; Chung, Kevin C.; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: This study performs an economic analysis of volar locking plate, external fixation, percutaneous pinning, or casting in elderly patients with closed distal radius fractures. Methods: This is a secondary analysis of the Wrist and Radius Injury Surgical Trial, a randomized, multicenter, international clinical trial with a parallel nonoperative casted group of patients older than 60 years with surgically indicated, extraarticular closed distal radius fractures. Thirty-Six-Item Short-Form Health Survey–converted utilities and total costs from Medicare were used to calculate quality-adjusted life-years and incremental cost-effectiveness ratio. Results: Casted patients were self-selected and older ( p < 0.001) than the randomized surgical cohorts, but otherwise similar in sociodemographic characteristics. Quality-adjusted life-years for percutaneous pinning were highest at 9.17 and external fixation lowest at 8.81. Total costs expended were 16, 354 for volar locking plates, 16, 012 for external fixation, 11, 329 for percutaneous pinning, and 6837 for casting. The incremental cost-effectiveness ratios for volar locking plates and external fixation were dominated by percutaneous pinning and casting. The ratio for percutaneous pinning compared to casting was 28, 717. Probabilistic sensitivity analysis revealed a 10, 5, 53, and 32 percent chance of volar locking plate, external fixation, percutaneous pinning, and casting, respectively, being cost-effective at the willingness-to-pay threshold of 100, 000 per quality-adjusted life-year. Conclusions: Casting is the most cost-effective treatment modality in the elderly with closed extraarticular distal radius fractures and should be considered before surgery. In unstable closed fractures, percutaneous pinning, which is the most cost-effective surgical intervention, may be considered before volar locking plates or external fixation.